1983
DOI: 10.1016/s0022-5347(17)52209-0
|View full text |Cite
|
Sign up to set email alerts
|

Primary Realignment of Posterior Urethral Injuries

Abstract: The records of 34 patients with posterior urethral disruptions secondary to blunt pelvic trauma who were treated with primary realignment were reviewed. Among the 29 evaluable patients there was a 38 per cent incidence of stricture (11 of 29), a 3 per cent incidence of incontinence (1 of 29) and a 15 per cent incidence of impotence (4 of 27). Primary realignment has a low morbidity and an acceptable rate of incontinence, impotence and stricture formation, and is recommended in the treatment of posterior urethr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The following arguments are specified for the procedure: lower rate of impotence, lower rate of incon tinence, simpler later treatment of the stricture [11]. On the other hand, there are the advocates of primary treat ment with exposure, drainage, realignment and possibly suture and adaptation of the urethral stumps [12][13][14], The advantages of this procedure are control of hemor rhage, drainage of hematoma and extravasate, lower scar formation, above all in prostatourethral dislocation, pos sibility of avoiding posttraumatic strictures [13]. In our series of heterogenous urethral lesions, the two groups (conservative/primary surgical care) are only compara ble to a limited extent.…”
Section: Discussionmentioning
confidence: 99%
“…The following arguments are specified for the procedure: lower rate of impotence, lower rate of incon tinence, simpler later treatment of the stricture [11]. On the other hand, there are the advocates of primary treat ment with exposure, drainage, realignment and possibly suture and adaptation of the urethral stumps [12][13][14], The advantages of this procedure are control of hemor rhage, drainage of hematoma and extravasate, lower scar formation, above all in prostatourethral dislocation, pos sibility of avoiding posttraumatic strictures [13]. In our series of heterogenous urethral lesions, the two groups (conservative/primary surgical care) are only compara ble to a limited extent.…”
Section: Discussionmentioning
confidence: 99%
“…Ying-Hao et al [13] evaluated 16 men who had bulbar urethral disruption with endoscopic realignment and reported that all cases were successfully treated in a single session without intraoperative or postoperative complications. However, so far, there is controversy regarding postoperative stricture, complications such as impotence and incontinence, and pelvic abscess [16-18]. With attempted urethral "realignment" over a urethral catheter, the rate of stenosis increases from -10 to -65% in incomplete disruption and from -75 to -100% in complete disruption [16].…”
Section: Discussionmentioning
confidence: 99%
“…In experienced hands, such an approach has been demonstrated to have better outcomes as compared to insertion of a suprapubic cystostomy alone. [21]…”
Section: Discussionmentioning
confidence: 99%